2013
DOI: 10.1088/0953-8984/25/37/375602
|View full text |Cite
|
Sign up to set email alerts
|

A temperature dependent tunneling study of the spin density wave gap in EuFe2As2single crystals

Abstract: We report temperature dependent scanning tunneling microscopy and spectroscopy measurements on single crystals of EuFe2As2 in the 15-292 K temperature range. The in situ cleaved crystals show atomic terraces with homogeneous tunnel spectra that correlate well with the spin density wave (SDW) transition at a temperature, TSDW ≈ 186 K. Above TSDW the local tunnel spectra show a small depression in the density of states (DOS) near the Fermi energy (EF). The gap becomes more pronounced upon entering the SDW state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Another optical investigation () on EuFe2As2 also does not show the second gap. Our earlier tunneling study () on EuFe2As2 also showed a single gap like spectra.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another optical investigation () on EuFe2As2 also does not show the second gap. Our earlier tunneling study () on EuFe2As2 also showed a single gap like spectra.…”
Section: Discussionmentioning
confidence: 94%
“…Some ARPES studies show an energy gap , while others do not show any gap in the SDW state. However, optical conductivity , quantum oscillation and scanning tunneling microscopy and spectroscopy (STM/S) () studies show an energy gap below the SDW transition. In pnictides, both SDW and SC originate from the same Fe d‐bands.…”
Section: Introductionmentioning
confidence: 99%
“…Also, as inferred from the results of infrared studies, short-range AF correlations have been suggested as being responsible for the pseudogap in iron superconductors [29,30]. Moreover, scanning tunneling microscopy (STM) studies have also seen an energy gap in the density of states near the Fermi energy [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…With its atomic scale structural and spectroscopic imaging capabilities, scanning tunneling microscopy and spectroscopy (STM/S) is an ideal probe to investigate the local electronic properties of these systems. In our variable temperature STM/S we investigate the tem- while we normalize the spectra for large bias (250 mV) to normalize away the effect of the tunnel matrix element on the spectra 22 . This process also sharpens the spectral features.…”
Section: Introductionmentioning
confidence: 99%